A new southern Atlantic cryptic marine shrimp species of Acetes (Decapoda, Sergestidae) - Bochini, Gabriel L.; Costa, Rogério C. [UNESP]; Mantelatto, Fernando L. (Pensoft Publishers, 2024)
A recently published molecular phylogenetic analysis, focusing on selected Western Atlantic subspecies of Acetes americanus Ortmann, 1893 and allies, was inconclusive about relationships among these members. This previous study found three groups that split into two distinct lineages: Acetes americanus (Brazil 1) (= A. americanus sen-su stricto) and Acetes americanus (Brazil 2) + A. americanus (USA). Combined mor-phometry and molecular analyses applied to members of the group Acetes americanus (Brazil 2) revealed a new unidentified species genetically related to the A. americanus representatives. However, at that time, no conclusive morphological characters were found to identify it. In the present study, following an in-depth morphological analysis of specimens from the three groups, including data on the type series and consideration of the subtle distinctions of members of each lineage, morphological features of the reproductive structures (petasma and genital sternite) were found to characterize the new species, which is formally described and named herein.
Keywords: Acetes americanus; Brazil; Cananéia; Dendrobranchiata; hidden diversity; new species; taxonomy